Alleviation of reactive oxygen species enhances PUFA accumulation in Schizochytrium sp. through regulating genes involved in lipid metabolism - Sai Zhang; Yaodong He; Biswarup Sen; Xiaohong Chen; Yunxuan Xie; Jay D. Keasling; Guangyi Wang (Metabolic Engineering Communications, 2018)
The unicellular heterotrophic thraustochytrids are attractive candidates for commercial polyunsaturated fatty acids (PUFA) production. However, the reactive oxygen species (ROS) generated in their aerobic fermentation process often limits their PUFA titer. Yet, the specific mechanisms of ROS involvement in the crosstalk between oxidative stress and intracellular lipid synthesis remain poorly described. Metabolic engineering to improve the PUFA yield in thraustochytrids without compromising growth is an important aspect of economic feasibility. To fill this gap, we overexpressed the antioxidative gene superoxide dismutase (SOD1) by integrating it into the genome of thraustochytrid Schizochytrium sp. PKU#Mn4 using a novel genetic transformation system. This study reports the ROS alleviation, enhanced PUFA production and transcriptome changes resulting from the SOD1 overexpression. SOD1 activity in the recombinant improved by 5.2–71.6% along with 7.8–38.5% decline in ROS during the fermentation process. Interestingly, the total antioxidant capacity in the recombinant remained higher than wild-type and above zero in the entire process. Although lipid profile was similar to that of wild-type, the concentrations of major fatty acids in the recombinant were significantly (p ≤ 0.05) higher. The PUFA titer increased up to 1232 ± 41 mg/L, which was 32.9% higher (p ≤ 0.001) than the wild type. Transcriptome analysis revealed strong downregulation of genes potentially involved in β-oxidation of fatty acids in peroxisome and upregulation of genes catalyzing lipid biosynthesis. Our results enrich the knowledge on stress-induced PUFA biosynthesis and the putative role of ROS in the regulation of lipid metabolism in oleaginous thraustochytrids. This study provides a new and alternate strategy for cost-effective industrial fermentation of PUFA. Keywords: Polyunsaturated fatty acids, Schizochytrium sp., Superoxide dismutase, Transgene, Transcriptomic analysis